Significação em processo de investigação de temáticas cotidianas: as experiências vivenciadas por estudantes surdos e uma surdocega no contexto escolar - CONTENTE, Márcia Pantoja (Universidade Federal do Pará, 2022)
In this thesis we present results obtained from qualitative research with action research elements, in the field research modality, aiming to understand the meanings produced by the participants about the experiences lived in the context of the scientific school culture, investigating everyday themes in situations collectives, with the aim of citizen participation. The participants of the research are eight deaf students and a deaf-blind student of the second phase of the Young and Adults Education (EJA) of fundamental school and two teachers of an University of Specialized Teaching of the state of Pará. As investigative tools to produce data we used forms; school documents; field journal of the researcher; video diaries of the students; testimony of the participants; and the video records. The data were built with information obtained by the reading and discussion of the story “Sofia, an investigative student”, of dialog moments about the scientific method of searching for a theme of investigation starting of the context where the students live, regarding the themes of investigation, internet searching, elaboration of panels about the investigation themes, and the process of orientation for the building of elements of investigation. The analysis of the obtained information was oriented by the assumption of the Discursive Textual Analysis, what has allowed the construction of the thematic axis: i. The student investigative process: the building of meaning in the school environment; ii. Of the challenges to the possibilities of leaning: a look towards of the investigation of everyday themes; and iii. Auto formative dimension: by a practice fulfilled of meanings. The obtained data of our insertion in the context of research reasoned by the ideas of Vygotski, Pozo and Crespo Goméz, Cachapuz, among others, allow us to infer that the deaf and the deaf-blind student, by the investigation of the everyday thematic, seek to proactively participate of the environment where they live, having as focus the role of the scholar institution as a space free for the production of meanings, and not as a environment of reproduction. By the approach of web research, the students had access of a rich and updated information source, motivating them to research in a way to deep their knowledges about the investigation thematic, allowing themselves to become protagonists of their own learning. Although present educational potential the technological resources in the school space, as manifested by the students themselves, remain restrict to the interest of the teachers. In the context of this research, the collective work was perceived as an efficient and potentially valid strategy for promoting a larger interaction among the students and them with the teachers, the ideas exchange, experiences, and knowledges regarding the investigated thematic, enriching the learning possibilities, and to promote the decision taking in relation of social problems present in the everyday. And, closing, the experience lived allowed the regent teachers to rethink their own teaching practice, envisioning a new educational movement that prioritize the student protagonism, and the role of mentors in the process of teaching and learning.